2019
DOI: 10.3390/rs11243025
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Split-Window Algorithm for Land Surface Temperature Retrieval from Sentinel-3A SLSTR Data Over Barren Surfaces Using ASTER GED Product

Abstract: Land surface temperature (LST) is a key variable influencing the energy balance between the land surface and the atmosphere. In this work, a split-window algorithm was used to calculate LST from Sentinel-3A Sea and Land Surface Temperature Radiometer (SLSTR) thermal infrared data. The National Centers for Environmental Prediction (NCEP) reanalysis atmospheric profiles combined with the radiation transport model MODerate resolution atmospheric TRANsmission version 5.2 (MODTRAN 5.2) were utilized to obtain atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
(54 reference statements)
1
18
0
Order By: Relevance
“…where , ′ and , ′ represent the generated BT and FVC, respectively; and represent the mean and standard deviation, respectively; and , −1 represents an inverse process of the Planck function from thermal radiance to BT. According to the uncertainty analysis in [30,45], the uncertainties associated with the angular variations in LST retrieval were considered by setting to 0.25 K and 0.75 K with = 0. Based on [46], angular errors in FVC were included by setting to 0 and to 0.03 and 0.09.…”
Section: ) Retrieval Noisementioning
confidence: 99%
See 1 more Smart Citation
“…where , ′ and , ′ represent the generated BT and FVC, respectively; and represent the mean and standard deviation, respectively; and , −1 represents an inverse process of the Planck function from thermal radiance to BT. According to the uncertainty analysis in [30,45], the uncertainties associated with the angular variations in LST retrieval were considered by setting to 0.25 K and 0.75 K with = 0. Based on [46], angular errors in FVC were included by setting to 0 and to 0.03 and 0.09.…”
Section: ) Retrieval Noisementioning
confidence: 99%
“…where 0 − 7 are the SW coefficients; 8 and 9 represent the top-of-atmosphere BTs in SLSTR channels 8 (10.85 μm) and 9 (12.0 μm), respectively; and ̅ and are the mean and the differences of emissivity 8, and 9, in SLSTR channels 8 and 9, respectively. In-depth details on the SW algorithm are readily found in the published literature [28,30,45,48]. The SW coefficients were determined by fitting (11) to a synthetic dataset obtained with MODTRAN 5.2 [49] for data from the ASTER spectral library [50] and Seebor V5.2 atmosphere profile library [51]: we used 81 emissivity spectra, including for natural samples of vegetation, water, ice, snow, rock, sand and soil, and 4948 daytime atmospheric profiles to obtain a globally representative data collection.…”
Section: B Atmospheric Correctionmentioning
confidence: 99%
“…Several validations have shown that this emissivity product has high accuracy over bare soil surface in arid and semi-arid lands [44], [45]. Therefore, to characterize the variation of bare soil emissivity relatively accurately, this dataset has been used in emissivity estimation for many satellites sensors [46]- [49].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most land surface temperature and sea surface temperature (LST and SST, respectively) products are based on multichannel methods. The split-window (SW) algorithm is widely used for TIR sensors, as it is easy to apply and can be used without extensive computation of radiative transfer models (RTMs) or explicit information of atmospheric conditions [1,[6][7][8][9]. However, these multi-channel methods have limited application in other types of single-channel-based IR sensors, such as LANDSAT-7 [10].…”
Section: Introductionmentioning
confidence: 99%